Characterization of GaAs Solar Cells under Supercontinuum Long-Time Illumination - Papež, Nikola (Materials (Basel), 2021)
This work is dedicated to the description of the degradation of GaAs solar cells under continuous laser irradiation. Constant and strong exposure of the solar cell was performed over two months. Time-dependent electrical characteristics are presented. The structure of the solar cells was studied at the first and last stages of degradation test. The data from Raman spectroscopy, reflectometry, and secondary ion mass spectrometry confirm displacement of titanium and aluminum atoms. X-ray photoelectron spectroscopy showed a slight redistribution of oxygen bonds in the anti-corrosion coating.